2011
DOI: 10.1007/s00449-011-0669-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of novel benzo[a]anthracene-degrading microorganisms and continuous bioremediation in an expanded-bed bioreactor

Abstract: In the present work, several samples from lab waste containers polluted with polycyclic aromatic hydrocarbons (PAHs) and heavy metals were investigated as potential sources of PAH-degrading microorganisms. After isolating, two fungal strains were selected as the best degrading microorganisms. Genetic identification by sequencing was carried out and they were identified as Trichoderma longibrachiatum and Byssochlamys spectabilis. Their degradation ability was determined in liquid cultures with 100 μM of benzo[a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Total BAA removal was obtained after 7 days. This fact is a promising result because less is known about the bacteria capable of utilizing PAHs containing four or more rings as a carbon and energy source, and it has been reported that only fungi can degrade these types of PAHs (Peng et al 2008;Rosales et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total BAA removal was obtained after 7 days. This fact is a promising result because less is known about the bacteria capable of utilizing PAHs containing four or more rings as a carbon and energy source, and it has been reported that only fungi can degrade these types of PAHs (Peng et al 2008;Rosales et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The polluted medium (PM) was composed of malt extract 3 g/L, yeast extract 3 g/L, Tween 80 1 %, acetone 2 % and 100 μM PAHs (Moscoso et al 2012a, b;Rosales et al 2012). In the experiment where the presence of metals was evaluated, this medium also contained 100 mg/L of Cr(VI).…”
Section: Polluted Mediamentioning
confidence: 99%
“…(1) was used to model the obtained data, in which D is the PAHs degradation degree at a specific moment of the time t, D 0 and D max are the initial and maximum degradation percentage, respectively, and l D is the maximum specific degradation rate (Rosales et al 2012).…”
Section: Growth and Biodegradation Assays In Flasksmentioning
confidence: 99%
“…Stability of PAHs in the soil is also dependent on the structure and properties of hydrocarbons [Banach-Szott et al 2012]. Usually, low-molecular-weight PAHs are easily degradable, but highmolecular weight PAHs, containing four or more aromatic rings, are considered resistant, thermodynamically stable and more difficult to degrade [Rosales et al 2012].…”
Section: Introductionmentioning
confidence: 99%